1991
DOI: 10.1090/s0002-9939-1991-1081099-3
|View full text |Cite
|
Sign up to set email alerts
|

On the subgroup separability of generalized free products of nilpotent groups

Abstract: Abstract.We prove that generalized free products of finitely generated nilpotent groups with cyclic amalgamation are subgroup separable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Consequently one might well expect a similar result for generalized free products of nilpotent groups. The paper [13] attempts to prove this result in the same fashion as [3] by establishing two propositions and then appealing to Lemma 1 of [3]. Unfortunately Proposition 3.5 of [13], whilst true, seems to be insufficient.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Consequently one might well expect a similar result for generalized free products of nilpotent groups. The paper [13] attempts to prove this result in the same fashion as [3] by establishing two propositions and then appealing to Lemma 1 of [3]. Unfortunately Proposition 3.5 of [13], whilst true, seems to be insufficient.…”
mentioning
confidence: 95%
“…The paper [13] attempts to prove this result in the same fashion as [3] by establishing two propositions and then appealing to Lemma 1 of [3]. Unfortunately Proposition 3.5 of [13], whilst true, seems to be insufficient.Counterexamples of the type claimed can readily be obtained by selecting suitable subgroups of the generalized free products constructed in [5]. Consider, for instance, G = A * a B where B = a, c : [a, c] = 1 and…”
mentioning
confidence: 95%
“…The first attempt to characterize subgroup separability of free products of nilpotent groups with cyclic amalgamation was made by Tang in [13]. Nevertheless, Allenby and Doniz [2] showed that Tang's result was incorrect, by constructing a counter-example.…”
mentioning
confidence: 99%